2015
DOI: 10.1590/1519-6984.12113
|View full text |Cite
|
Sign up to set email alerts
|

Gonad development and reproduction of the ballyhoo half beak, Hemiramphus brasiliensis from the coastal waters of Rio Grande do Norte, Brazil

Abstract: The gonad development and reproductive aspects of Hemiramphus brasiliensis from the coastal waters of Rio Grande do Norte, Brazil were verified. This paper presents data on the length-weight relationship, sex ratio, length at first sexual maturity, gonad development, reproductive period and fecundity of H. brasiliensis. Females of this species predominated in the sampled population and were larger in size than the males. The length at the first sexual maturation of males was 20.8 cm and that of females was 21.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…However, we find the latter unlikely, as females of M. alexandrini, M. mola and Ma. lanceolatus appear to grow much larger than males (Liu et al ., 2009; Sawai et al ., 2011, 2018a), as also seen in some other teleost species ( e.g ., Oliveira et al ., 2015; Shimose et al ., 2009). For M. alexandrini , no males > 200 cm L T have been reported (Sawai et al ., 2011, 2018a); both sexed specimens in this study were female, aligning with this notion.…”
Section: Discussionmentioning
confidence: 99%
“…However, we find the latter unlikely, as females of M. alexandrini, M. mola and Ma. lanceolatus appear to grow much larger than males (Liu et al ., 2009; Sawai et al ., 2011, 2018a), as also seen in some other teleost species ( e.g ., Oliveira et al ., 2015; Shimose et al ., 2009). For M. alexandrini , no males > 200 cm L T have been reported (Sawai et al ., 2011, 2018a); both sexed specimens in this study were female, aligning with this notion.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, Oktaviani et al (2018) studied biological aspects of Pentaprion longimanus, and found that the mature fish length ranged between 7.4 to 15.3cm. Oliveira et al (2015) studied on Hemiramphus brasiliensis and reported that the length at the first sexual maturation of males was 20.8cm. .…”
Section: Discussionmentioning
confidence: 99%
“…The dissection process allowed a macroscopic description of the gonads for each specimen Oliveira et al, 2015). Histology analysis for each A. scapularis specimen tissue ovaries sample was performed.…”
Section: Macroscopic and Histological Analysis Of The Ovariesmentioning
confidence: 99%